IMPLEMENTASI MODEL EXPERIENTIAL LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KEPADA GENERASI-Z DI SMK YAYASAN ISLAM TASIKMALAYA - Ighni Raihani; Ade Zaenul Mutaqin (Program Studi Pendidikan Agama Islam, 2025)
This study aims to enhance students' learning interest in Islamic Religious Education (PAI) through the implementation of the Experiential Learning model at SMK Yayasan Islam Tasikmalaya. The background of the study stems from the low student engagement caused by the dominance of monotonous lecture-based teaching methods that lack active student participation. Employing a Classroom Action Research (CAR) approach over two cycles—each consisting of planning, action, observation, and reflection—data were collected through observation, interviews, questionnaires, and documentation. The results indicate a significant improvement in students’ average scores, rising from 64.8 in the first cycle to 76.9 in the second, along with increased enthusiasm, active participation, and positive attitudes toward PAI learning. The Experiential Learning model, which emphasizes direct experience, critical reflection, and the application of Islamic values in real-life contexts, proved effective in creating a more meaningful and enjoyable learning process. This study concludes that innovative, experience-based learning methods are essential in teaching Islamic Religious Education to foster student interest and holistically develop character in the context of 21st-century education